2017
DOI: 10.1111/scs.12426
|View full text |Cite
|
Sign up to set email alerts
|

Support provided by nurses to parents of hospitalized children – cultural adaptation and validation of Nurse Parent Support Tool and initial research results

Abstract: Support provided by nurses to parents of hospitalized childrencultural adaptation and validation of Nurse Parent Support Tool and initial research resultsIntroduction: Child's illness and hospitalisation are difficult and stressful situations both for the patients themselves and for their parents. Supporting the ill child and their guardians is an indispensable element of caring for ill children. The Nurse-Parent Support Model developed by Margaret Miles is based on four elements, namely emotional support, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 53 publications
3
14
2
1
Order By: Relevance
“…In the study, the subscale Support for Communication and Information obtained the lowest average, similar to studies developed in USA 21 , Poland 22 , and Turkey 23 in which this item also obtained low scores. This shows weakness in the team's communication relationship with mothers and a gap in the quality of care provided, emphasizing the need to continue applying the PNH guidelines in Brazilian health services [24][25][26] .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In the study, the subscale Support for Communication and Information obtained the lowest average, similar to studies developed in USA 21 , Poland 22 , and Turkey 23 in which this item also obtained low scores. This shows weakness in the team's communication relationship with mothers and a gap in the quality of care provided, emphasizing the need to continue applying the PNH guidelines in Brazilian health services [24][25][26] .…”
Section: Discussionsupporting
confidence: 82%
“…Emotional Support was well evaluated and ranked second in the NPST subscales, in contrast to other studies in the USA 21 and Poland 22 , in which it was poorly evaluated. However, a study developed in China obtained a result similar to that found in the present study, which may represent a cultural difference about the care provided by the nursing staff to mothers or about the mothers' perception of emotional support 31 .…”
Section: Discussioncontrasting
confidence: 81%
“…Due to the low value of Cronbach's alpha, an attempt to verify items that constitute the ISEL-40 v.GP was made to improve internal consistency of the entire scale and its subscales. Revision of the items that make up the scale and the removal of 8 items of the tool (1,4,6,8,22,24,36,40) only slightly improved its internal consistency (α=0.87). In the case of the Tangible support subscale, no removal of any items improved the internal consistency of the tool (α=0.79).…”
Section: Methodsmentioning
confidence: 99%
“…Research results suggest that supporting interventions ought to be aimed mainly at mothers [23]. Nevertheless, some research indicates that there is no link between the gender of the researched individuals and their perception of support provided by nursing staff [24].…”
Section: Introductionmentioning
confidence: 97%
“…25 However, it was found by a study carried out in Poland, assessing the perception of parents of hospitalized children about the nursing care provided to them, that the family members considered the instrumental support given by nurses as unsatisfactory. 26 It is warned that, in Brazil, there is familycentered care in pediatric health institutions, but lacking major expression, so, in the hospital environment, there is a predominance of isolated actions taken by practitioners who give attention to the family because they are emotionally moved by its situation. 25 Thus, the family-centered care approach shows to be needed in vocational education courses, either at High School technical education, undergraduate, and graduate levels, and/or in refresher courses, offering curricular components on the theme and presenting the positive impacts that this knowledge brings to professional practice.…”
Section: It May Be Indicated That Neuman's Systemsmentioning
confidence: 99%